Exploded views: early cinema and the spectacular logic of the explosion. (19th December 2018) - Duncan, Pansy
Abstract: In this essay I advance a simple but striking argument about the eruptive, explosive blasts that formed the primary attraction of the early cinematic 'explosion film' – a little-discussed species of trick film that was briefly in vogue between 1900 and 1903. I contend that, while regularly cast as a destructive object of vision that serves primarily as a spark to spectatorial kinesis, the explosion is also a productive technology of vision that serves to deliver the world more readily to view – and that, as such, the explosion has played a key role in the emergence and evolution of the language of film spectacle. Drawing both on extant examples of the explosion film, and on relevant archival, historical and theoretical evidence, I advance this argument in three stages. First I establish a homology between the monstrative affordances of the cinematic spectacle and the monstrative affordances of the explosion. Then I show that, between 1900 and 1903, the fledgling film industry was running up against the limitations of its capacity to deliver on its own monstrative promise – the promise, as Méliès's 'Star Films' slogan had it, to deliver 'The Whole World Within Reach'. Finally, situating the explosion film against the backdrop of these limitations, I argue that, in the absence of well-established formal strategies of monstration, the explosion's capacity to isolate, disintricate and arrest objects for view saw it enlisted as a kind of 'cinematic prosthesis', enabling it to serve, initially, as surrogate for these strategies, and, ultimately, as a model for their development.